Measuring Growth Driving Supply Chain Integration (Gdsci) Factors Using Confirmatory Factor Analysis (Cfa) At The Gresik Petrochemical Bulk Terminal - Bagusranu Wahyudi Putra; Whidya Utami; Murpin Josua Sembiring Gurky (Journal of Social Research, 2025)
The growth of the bulk port industry increasingly demands more effective supply chain integration to enhance competitiveness and operational efficiency. This study examines the growth-driving factors in Growth Driving Supply Chain Integration (GDSCI) at Petrokimia Gresik Bulk Port using Confirmatory Factor Analysis (CFA). The research model evaluates three main dimensions of GDSCI: Collaborative Competitive Advantage (CCA), System Resilience (SR), and System Stakeholder Satisfaction (SSS). The CFA results indicate that all indicators have loading factors above 0.70, except for one indicator that still meets the convergent validity tolerance threshold. The Goodness-of-Fit (GOF) index demonstrates that the model has a good fit with empirical data, with values of GFI = 0.952, CFI = 0.954, and RMSEA = 0.092. These findings confirm that supply chain integration plays a crucial role in improving logistics efficiency, Collaborative competitiveness, and stakeholder satisfaction. The results support the Dynamic Capability Theory, which emphasizes the importance of dynamic capabilities in dealing with market uncertainty and changes in the business environment. Practically, this study provides insights for port managers and regulators to optimize supply chain integration strategies to enhance operational performance and long-term business growth. The study also recommends strengthening stakeholder collaboration and leveraging digital technology to improve the resilience of the logistics system.